ASUHAN KEPERAWATAN PADA An.Z DENGAN POST OP APPEDISITIS DI RUANG KHADIJAH 2 RSUD BANGKINANG - Aprilliana hesti Hesti; Ridha Hidayat; Dewi Sulastri Juwita Dewi (El-Emir Institute, 2025)
Appendicitis is an inflammation caused by infection and requires appendectomy surgery in its treatment procedure. The purpose of this study is to carry out nursing care in patients with post-op appendicitis in the Khadijah 2 room of Bangkinang Regional Hospital in 2025. This study uses a descriptive method in the form of a case study with data collection methods used, namely interviews, observations, physical examinations, data collection and documentation. Data obtained through interviews, physical examinations and supporting examinations. During the assessment, the patient said pain in the lower right quadrant surgical scar, pain appears during activity, pain appears suddenly, pain feels like being stabbed. So that researchers can formulate the main problem with the nursing diagnosis of acute pain related to physiological injury agents (surgical procedures) (D. 0007). The nursing implementation provided non-pharmacological techniques to reduce pain through deep breathing relaxation techniques. This case report is intended to provide or serve as a reference in nursing care for children with post-op appendicitis.